Analysis of Humanistic Learning Theory in Al-Ghazali's Thought: A Study of the Book Ayyuhal Walad - Qoffal, Sholahuddin; Laisa, Emna (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This research seeks to examine the alignment of humanistic learning theory within the philosophical perspective of Imam Al-Ghazali, particularly as reflected in his work Ayyuhal Walad. It explores how the Sufi educational values conveyed by Al-Ghazali correspond with the core principles of humanistic learning—such as the cultivation of personal potential, spiritual consciousness, and the positioning of learners as active participants in their educational journey. Employing a qualitative approach, this study utilizes library research and content analysis methods to interpret the messages in Ayyuhal Walad, supplemented by theoretical insights from key humanistic scholars like Abraham Maslow and Carl Rogers. The findings indicate a significant congruence between Al-Ghazali’s educational outlook and the framework of humanistic learning, especially regarding the emphasis on individual experience, value internalization, and the nurturing of moral awareness. Al-Ghazali views education not merely as a vehicle for acquiring academic success, but as a transformative process that fosters ethical and spiritual development.Thus, this study underscores the potential of Al-Ghazali’s educational thought to serve as a foundational model for constructing a humanistic approach to Islamic education—one that deeply engages with the full spectrum of human experience and personal growth